Reproductive Biology of Coral Catshark Atelomycterus marmoratus (Anonymous [Bennett], 1830) in Seribu Islands, Indonesia - Selvia Oktaviyani; WANWAN KURNIAWAN; FAHMI (Biodiversitas Journal of Biological Diversity, 2019)
This study provides information on the reproductive biology of the coral catshark caught in the waters around Seribu Islands, Indonesia. A total of 257 coral catsharks were collected from February 2017 to January 2018. The total length of coral catshark ranged from 170 to 585 mm for females and 255-575 mm for males, respectively. The total weight of females ranged from 85 to 640 g and males from 100 to 620 g The sex ratio between females and males was 0.45 and it was not significantly different from the expected 1:1 ratio. The growth pattern of coral catsharks in Seribu Island was negatively allometric and the population was dominated by mature sharks. The mean size at first maturity was estimated to be 557 mm for females and 514 mm for males, based on to the relationship between the proportion between maturity stage and total length. The ovulation season was estimated occur from October to March, whereas September to April was mating season based on monthly variations of gonadosomatic index (GSI) values and the occurrence of egg cases in uterus.